Main Tendencies of Healthcare System Development of Northern Bukovyna and Khotyn Region during the Interwar Period - Rusnak, Oleksandr (Chernivtsi National University, 2021)
In the article the author characterizes main tendencies of healthcare system development of Northern Bukovyna and Khotyn region in 1918-1940. Investigates the state of sanitary and hospital services, covers the problem of combating epidemic diseases. Lack of qualified and well-timed care for patients with smallpox, typhus, tuberculosis, dysentery and other diseases that became widespread after World War I, led to an increase in mortality among the population. However, over time, the normal work of medical institutions has been restored and the threat of epidemics has been eliminated, and the number of diseases and deaths has decreased significantly. By 1921, the health care system of Northern Bukovyna and Khotyn region was almost completely in line with that in the Old Kingdom. However, the payment for treatment remained. For the most part, in 1918-1940, after receiving new equipment, continued to operate medical institutions established during the period when Bukovyna was a part of Austria-Hungary. According to the needs of time, their structure, number and qualification of medical staff was changing. New branches, laboratories and institutes were being opened on their basis. The pharmacy network was developing, societies of doctors and pharmacists were working, and county councils of hygiene were functioning. While noting some of the undoubted successes in the health care system of the region during this period, it should be noted that a large number of the rural population (especially the inhabitants of mountainous areas) did not have access to medicine.
Keywords: Northern Bukovyna, Khotyn region, diseases, sanitary condition, hygiene, hospital, epidemic